Cultivating Early Childhood Success: Kindergarten Teachers’ Professional Needs, Experiences, Efficacy Beliefs, and Performance - Tulang, Marichu D. (International Journal of Membrane Science and Technology, 2023)
This quantitative study delves into the relationship between kindergarten teachers’ professional needs, experiences, efficacy beliefs, and their overall performance. Using survey questionnaires, this descriptive study gathered data from 101 kindergarten teachers selected from various districts of the Department of Education within the Division of Butuan City. The findings of the study indicate that several factors are significantly related to teachers’ performance, including classroom management, professional experiences related to learning assessment, family engagement, learning outcomes, and self-management efficacy beliefs. Additionally, the study identified a predictive framework comprising inclusive education, family engagement, learning outcomes, and self-management variables, which play key roles in determining teachers’ performance. The implications of these findings suggest the need for the development of seminar workshops and program training designed to address the specific needs of kindergarten teachers, particularly considering that many teachers in the Butuan City Division are young and early in their careers. Such initiatives can contribute to enhancing teacher effectiveness and ultimately foster early childhood success.